Pengimplementasian Program CEMARA (Cendekia Muda Berkarakter) di Desa Kalipang dengan metode Community Based Participatory Research - Pebrianti, Vitriya Asih; Anggraini , Novia Afriana; Putri , Anggila Ruly Eka; Sasmita, Vania Rachma Wahyu; Jatmiko, Jatmiko (Universitas Nusantara PGRI Kediri, 2024)
The CEMARA Program is a program aimed at improving the academic skills and character of children in the village of Kalipang. The program is implemented using the Community-Based Participatory Research (CBPR) method that actively involves the community in the program planning, implementation, and evaluation process. The parties involved in the implementation of this program include the PM PM PM team, the Regional Government, Karang Taruna, as well as the children of the village of Kalipang. The implementation phase of the program includes planning, observation, and implementation.